SlMYC2 mediates stomatal movement in response to drought stress by repressing SlCHS1 expression - Xu, Bing-Qin; Wang, Jing-Jing; Peng, Yi; Huang, Huang; Sun, Lu-Lu; Yang, Rui; Suo, Lin-Na; Wang, Shao-Hui; Zhao, Wen-Chao (Frontiers in Plant Science, 2022)
Drought stress limits plant development and reproduction. Multiple mechanisms in plants are activated to respond to stress. The MYC2 transcription factor is a core regulator of the jasmonate (JA) pathway and plays a vital role in the crosstalk between abscisic acid (ABA) and JA. In this study, we found that SlMYC2 responded to drought stress and regulated stomatal aperture in tomato (Solanum lycopersicum). Overexpression of SlMYC2 repressed SlCHS1 expression and decreased the flavonol content, increased the reactive oxygen species (ROS) content in guard cells and promoted the accumulation of JA and ABA in leaves. Additionally, silencing the SlCHS1 gene produced a phenotype that was similar to that of the MYC2-overexpressing (MYC2-OE) strain, especially in terms of stomatal dynamics and ROS levels. Finally, we confirmed that SlMYC2 directly repressed the expression of SlCHS1. Our study revealed that SlMYC2 drove stomatal closure by modulating the accumulation of flavonol and the JA and ABA contents, helping us decipher the mechanism of stomatal movement under drought stress.